The Effect of Intellectual Capital on the Financial Performance of Deposit Money Banks in Nigeria. - Ofurum, Clifford Obiyo; Oyintonefie, Etonye; Fubara, Siminalayi; Azuike, Ngozi (Advances in Social Sciences Research Journal, 2023)
This study evaluates the relationship between intellectual capital and Nigerian deposit money banks' financial performance. Specifically, it aims to establish nexus between two proxies of intellectual capital, structural and human capital, and two facets of financial performance, return on assets and earnings per share. All the deposit money banks registered in the Nigerian stock exchange constitute the study population; however, only eight banks that published the required data between 2012 and 2020 were sampled. The study adopted Pulic's (2004) method of measuring intellectual capital and Hamdan's (2018) and Ozkan et al. (2016) model specifications. The model and collected data were analysed using simple regression analysis. The research revealed a significant relationship between structural capital and return on asset (ROA). It also found a significant association between human capital and earnings per share (EPS). Based on the result, we recommend that Nigerian bank managers and policymakers integrate intellectual capital into their decision-making process and pay more attention to this alternative source of capital to enhance their financial performance. Also, the management of banks should provide a conducive work environment, improve the welfare packages of their staff and ensure an excellent in-house training program.